Still-Living – Memory and Persistence in the Photographic Repertoires of the Living Theatre (Altre Modernità, 2025)
Between 1975 and 1983 The Living Theatre's work was punctuated by five new productions (Prometheus at the Winter Palace, Masse Mensch, The Yellow Methuselah, The Archaeology of Sleep and the revival of Antigone of Sophocles, which had premiered in 1967) and thirty performances of the cycle The Legacy of Cain: 810 performances, 622 in the theatre and 186 on the street, reaching almost 400,000 spectators. These were the years of the proverbial European nomadism but, in spite of the assumed precariousness, it was also a historical period exceptionally rich of memories, if we look at the collections that followed one after the other methodically in those same years and then flowed into the Italian archives dedicated to the company. The Cathy Marchand Fund, created in 2016, is a striking example: thanks to the donations of the Living Theatre actress, the fund is now preserved in the Lino Miccichè Arts Library of the Università degli Studi Roma Tre. The intervention therefore proposes to present different ways of approaching the photographic apparatus of the Fund, which consists of approximately 500 pictures: a plurality of authorships and perspectives, sources of as many possible trajectories of investigation. Starting from the cross-analysis of the two repertoires (spectacular and photographic), the archival impulse will be explored in dialogue with the diaristic notation, the production, conservation and publication of these photographic documents.
Keywords: Living Theatre; theatre, archive; photography; repertoire; performing arts